HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN MOTORIK PADA ANAK USIA 3 – 5 TAHUN - Mimi Ruspita; Khobibah Khobibah (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
An important period in growth and development is the toddler period, so that the slightest abnormality or deviation if it is not detected and not handled properly, will reduce the quality of human resources in the future. (Ministry of Health RI, 2016). A preliminary study conducted in Bandengan village in early 2019 on 5 children under five with malnutrition status, 3 children (60%) experienced delays in fine motor aspects, 2 children (40%) experienced delays in gross motor aspects. The purpose of this study was to determine the relationship between nutritional status and gross and fine motoric development. Quantitative research method with cross sectional approach. The population of all children aged 3-5 years in Bandengan village, Kendal Regency who meets the inclusion and exclusion criteria is 144 people as a sample. Univariate data analysis with frequency distribution and bivariat analysis with Chi Square test with α 0,05. The results showed that there was a significant relationship between nutritional status and gross motor skills of children aged 3-5 years where the p value was 0.001 α 0,05, and there was a significant relationship between nutritional status and fine motor skills of children aged 3-5 years with p value 0.001 α 0,05